Kajian Hukum Pasal 340 Jo Dan Pasal 351 Ayat 3 KUHP - Thereza Dwi Ningrum Siburian; Nadira Zawani; Reh Bungana Beru PA; Maulana Ibrahim (LPPM Universitas Sains dan Teknologi Komputer, 2023)
This research aims to analyze premeditated murder of Medan State Polytechnic students who committed acts of abuse and resulted in death. This research uses normative legal research with a statutory approach and a case approach. With step (1) Identify the legal facts that are applied. (2) collect legal materials. (3) conduct a review of legal issues. (4) draw conclusions. The research results are based on Article 340 Jo and Article 351 paragraph 3 of the Criminal Code that First, the position of the case has described criminal events, criminal acts and criminal acts. second, to punish students who commit premeditated murder and abuse.